PBL Online Learning in Thermodynamics and Statistical Physics: Students’ Readiness - Elnetthra Folly Eldy; Fauziah Sulaiman (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
This paper explores students’ readiness towards PBL online learning in two subjects of Physics among Physics students from Universiti Malaysia Sabah. Online learning was implemented through Problem-Based Learning (PBL) approach in two subjects, i.e., Thermodynamics Physics and Statistical Physics each during on Semester 1 and 2 respectively. A set of questionnaires was distributed to twenty five (25) second-year students of Physics with Electronics at University Malaysia Sabah before and after online learning was implemented for 28 weeks long. As a supplement, an interview was held with selected group of students from this sample to study students’ technical and pedagogical readiness which was discussed in this paper. As a conclusion, results of this paper lays the general foundation for active implementation of PBL online in topics of Physics in Universiti Malaysia Sabah.